Contribution of cats and dogs to SARS-CoV-2 transmission in households - Fischer, Egil A. J.; Broens, Els M.; Kooistra, Hans S.; De Rooij, Myrna M. T.; Stegeman, Jan Arend; De Jong, Mart C. M. (Frontiers in Veterinary Science, 2023)
SARS-CoV-2 is known to be able to jump across species. Occurrence of transmission in households between humans and companion animals has been shown, but the contribution of companion animals to the overall transmission within a household is unknown. The basic reproduction number (R¬¬0) is an important indicator to quantify transmission. For a pathogen with multiple host species like SARS-CoV-2, the basic reproduction number needs to be calculated from the partial reproduction numbers for each combination of host species. In this study, the basic and the partial reproduction numbers for SARS-CoV-2 were estimated by reanalysing a survey of Dutch households with dogs and cats with minimally one SARS-CoV-2 infected human. For households with cats, a clear correlation between the number of cats and the basic reproduction number (spearman ρ 0.40, p-value 1.4 x 10-5) was identified, while for dogs the correlation was smaller and not significant (spearman ρ 0.12 , p-value 0.21). Partial reproduction numbers from cats or dogs to humans were 0.3 (0.0-2.0) and 0.3 (0.0-3.5) and from humans to cats or dogs were 0.6 (0.4-0.8) and 0.6 (0.4-0.9). Thus the estimations of within-household transmission indicated the likelihood of transmission from these companion animals to humans, and vice versa, but the observational nature of this study hampered conclusive evidence. This study’s findings support the advice given during the pandemic to COVID-19 patients to keep distance from companion animals following the precautionary principle and given transmission might occur, but with an overall relatively limited impact on the pandemic when compared to human-to-human transmission.